John Polkinghorne: Science and Religion from the Viewpoint of Theoretical Physics - Monserrat Puchades, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2012)
This article presents, comments on, and discusses the thought of John Polkinghorne. Aftera biographical sketch and a presentation of his contribution to the science-religion dialogue from the view point of theoretical physics, the article analyzes his epistemology, his evaluation of some ideas ofclassical metaphysics, his analysis of the likeliness of the creative fundamentality of God, the coherenceof the evolutionary, living, and human world with the idea of God, as well as the likeliness of divineaction in the world from the viewpoint of quantum mechanics and the dynamics of chaos. The articleends with the concept and dimensions of kenotic creation. In the course of the discussion, the articlealso deals with topics such as Polkinghorne’s view on panentheism, double-aspect dualism, emergentism,divine action, active information, kenotic creation, and so forth.